Transactions on Data Hiding and Multimedia Security VII - Shi, Yun Q.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
Since the mid 1990s, data hiding has been proposed as an enabling technology for securing multimedia communication, and is now used in various applications including broadcast monitoring, movie fingerprinting, steganography, video indexing and retrieval, and image authentication. Data hiding and cryptographic techniques are often combined to complement each other, thus triggering the development of a new research field of multimedia security. Besides, two related disciplines, steganalysis and data forensics, are increasingly attracting researchers and becoming another new research field of multimedia security. This journal, LNCS Transactions on Data Hiding and Multimedia Security, aims to be a forum for all researchers in these emerging fields, publishing both original and archival research results. The 7 papers included in this issue deal with the following topics: protection of digital videos, secure watermarking, tamper detection, and steganography.
An Efficient Robust Watermarking Method Integrated in H.264/SVC -- PC-Based Real-Time Video Watermark Embedding System Independent of Platform for Parallel Computing -- IR Hiding: Method for Preventing Illegal Recording of Videos Based on Differences in Sensory Perception between Humans and Devices -- Secure Watermarking on 3D Geometry via ICA and Orthogonal Transformation -- Measuring the Statistical Correlation Inconsistencies in Mobile Images for Tamper Detection.-Secure Steganography Using Randomized Cropping -- Steganography in Streaming Multimedia over Networks.
Keywords: Computer science; Computer Communication Networks; Data protection; Data encryption (Computer science).; Computer software; Optical pattern recognition; Computer Science; Systems and Data Security; Computer Communication Networks; Data Encryption; Algorithm Analysis and Problem Complexity; Computers and Society; Pattern Recognition